The outcomes of postoperative total hip arthroplasty following Western Ontario McMaster Universities Osteoarthritis Index (WOMAC): A prospective study - Tran Trung Dung; Pham Trung Hieu; Nguyen Thi Thuy Dung (Archives of Nursing Practice and Care - Peertechz Publications, 2018)
Objectives: Evaluation of the quality of life for patient with total hip arthroplasty surgery (THA) and whether patients with poor function before THA have the ability to recover less than those with less preoperative disability. Subjects and methods: A prospective study evaluated the preoperative and 3-month postoperative health-related quality of life score of 41 patients with THA due to hip osteoarthritis (OA) and femoral head necrosis (FHN) in Hanoi Medical University Hospital from February 201 to November 2017. The study divided into 2 function groups following the median preoperative Western Ontario McMaster Universities Osteoarthritis Index (WOMAC) physical function scores. Results: Average age is 53.78± 8.95. Male/female ratio is approximately 3: 1. 87.8% patients with femoral head necrosis situation. 100% patients had good health related to quality of life. However, low function group improves more signifi cantly than high function group. In addition, the proportion of normal number patients after 3 months of THA between low and high function group was 20.38%, and 23.53%, respectively for WOMAC physical functioning. Conclusion: Total hip arthroplasty surgery signifi cantly improves patient health and well-being. THA surgery helps patients improve signifi cant quality of life regardless the level of physical functioning before surgery.